Clinicopathological and Prognostic Significance of Cancer Stem Cell Markers in Ovarian Cancer Patients: Evidence from 52 Studies - Tao, Yifeng; Li, Hui; Huang, Rongyong; Mo, Dan; Zeng, Tian; Fang, Min; Li, Meiqin (Cellular physiology and biochemistry, 2018)
Background/Aims: Relevant markers of cancer stem cells (CSCs) may serve as commonly used biomarkers of ovarian cancer (OC). However, their actual clinicopathological and prognostic significance remains inconclusive. Thus, we conducted a meta-analysis to quantitatively evaluate the association between the expression of CSC-relevant markers (ALDH1, CD117, CD133, and CD44) and OC. Methods: We used an odds ratio (OR) and a hazard ratio (HR) with a 95% confidence interval (CI) to estimate the effects by analyzing 52 studies from a literature search. Heterogeneity and sensitivity were evaluated, as well. Publication bias was assessed using funnel plots and Egger tests. Results: ALDH1 expression was statistically associated with FIGO stage (OR=1.872, 95%CI=1.14-3.076, P=0.013) and lymph invasion (OR=2.78, 95%CI=1.08-7.152, P=0.034). CD117 expression was significantly associated with FIGO stage (OR=2.01, 95%CI=1.35-2.98, P=0.001). CD133 expression was correlated with FIGO stage (OR=3.410, 95%CI=2.196-5.294, P< 0.001) and differentiation grade (OR=2.672, 95%CI=1.354-5.272, P=0.005). CD44s was related to chemotherapy resistance (OR=3.218, 95%CI=1.148-9.016, P=0.026). Furthermore, overexpression of ALDH1 (HR=1.494, 95%CI=1.207-1.849, P< 0.001), CD117 (HR=1.395, 95%CI=1.025-1.898, P=0.034) or CD44s (HR=1.725, 95%CI=1.135-2.623, P=0.011) was associated with poor OS. Further, overexpression of both ALDH1 (HR=1.524, 95%CI=1.158-2.007, P=0.003) and CD44s (HR=2.12, 95%CI=1.692-2.657, P< 0.001) was correlated with worse DFS. Conclusion: CSC markers are useful predictive or prognostic biomarkers for OC in clinical assessments. Combined detection of CSC marker expression may be a powerful tool for prognostic predictions in clinical practice for patients with OC.